STEM Integrated Sciencepreneurship in Science Learning to Shape the Entrepreneurial Character of the Z Generation - Lutfi Lutfi; Akhmad Kurnia; Jusman Tang; Risma Haris (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2023)
The character of entrepreneurship is a character that must be cultivated from school age to form the attitude and mentality of students, therefore it is necessary to adapt learning to the needs of the current of the Z generation. The research aims to apply STEM learning integrated sciencepreneurship in the students of the 8th grade MTs Nurul Izzah Kalamisu as the Z generation to shape the character of entrepreneurial from school age. Research design using one case study, data collection using questionnaires and observations, data analysis is carried out using descriptive quantitative analysis. Research results show that 64% of students agree with STEM learning integrated sciencepreneurship, this learning is able to shape the student’s entrepreneurial character that includes confidence, task- and outcome-oriented, daring to take risks, spirit of leadership, having originality and future oriented.